Pelvic limb reconstruction failed by propeller flap resolved with microsurgery - Gómez-Mendoza, Francisco Fabián; Banegas-Ruíz, Rodrigo; Mendoza-Aceves, Rodrigo A.; Román-Hernández, Rigoberto; Porras-Méndez, Christian; Valderrama-Treviño, Alan I.; Uriarte-Ruíz, Karen; Vejar Alba, Ismael; Olivares Ulloa, Rubén; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2019)
Reconstruction of lower limb defects is a constant challenge for surgeons, the etiology of the defect can be very variable from diabetic ulcers, traffic accidents, fall from height, oncological resections and many others. Free flaps have always been an important option because it has great results in complex reconstructions in lower limbs, it is a microvascular technique, so it has a higher level of complexity. This technique is usually reserved for extensive perilesional wide defects. On the other hand, the propeller flap, which is considered less invasive and easier as it does not involve microvascular surgery. An 18-year-old patient who had a fracture of the right tibial pylon due to a 7-meter drop, who after orthopedic treatment had a defect with exposure of ostesynthesis material of 3 cm in circumference in the medial malleolus. This defect was first managed with a propeller flap complicated with necrosis at 48 hours which was treated with sub atmospheric pressure system for 5 days and later with an ultra-thin anterolateral flap of the pelvic limb. Complete pedicled propeller flap failure is very rare but, because necrosis develops distally, even partial necrosis can expose bone, tendons, or other tissue. Some surgeons consider that propeller flap placement is risky in this location, especially the distal third of the lower leg a prefer to use free flaps. Whenever any pelvic member reconstruction plan fails in the distal third, the best and safest is the use of microsurgery even with the failure of a previous micro vascular flap.